2021
DOI: 10.1088/1402-4896/ac33fc
|View full text |Cite
|
Sign up to set email alerts
|

Power improvement in ridge bent waveguide superluminescent light-emitting diodes based on GaN quantum dots

Abstract: In this paper, the performance of ridge-waveguide superluminescent light-emitting diodes (SLED) based on nitride quantum dots has been reported. For this purpose, the three-dimensional Schrodinger equation has been solved numerically by the finite volume method for truncated pyramidal quantum dots as active regions taking into account all spontaneous and piezoelectric effects. To calculate the modal gain in the active region, the traveling-wave rate equations model has been used. We solved the traveling-wave e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Moreover, Chua et al prepared a phosphorus-free pyramidal InGaN/GaN QD white-light LED and discovered that the internal quantum efficiency of the QD reached up to 50% at room temperature [290]. In another study, Rokhi et al evaluated a ridge waveguide super-radiance LED based on truncated pyramidal GaN QDs and observed that QDs with an uneven size distribution produced larger spectral widths, thereby leading to higher output powers [291]. They also found that the output power of the ridge waveguide super-radiance LED decreased with an increase in temperature (Figure 27).…”
Section: Luminescent Devices Based On Pyramidal Low-dimensional Semic...mentioning
confidence: 99%
“…Moreover, Chua et al prepared a phosphorus-free pyramidal InGaN/GaN QD white-light LED and discovered that the internal quantum efficiency of the QD reached up to 50% at room temperature [290]. In another study, Rokhi et al evaluated a ridge waveguide super-radiance LED based on truncated pyramidal GaN QDs and observed that QDs with an uneven size distribution produced larger spectral widths, thereby leading to higher output powers [291]. They also found that the output power of the ridge waveguide super-radiance LED decreased with an increase in temperature (Figure 27).…”
Section: Luminescent Devices Based On Pyramidal Low-dimensional Semic...mentioning
confidence: 99%